Relevansi Macam-Macam Pendekatan Pembelajaran Abad 21 terhadap Kebutuhan Siswa di Era Revolusi Digital - Chairunisa Mardiah Ramadhani; Dimas Julian Pratama; Rakha Agusti Amanullah; Sani Safitri; Rani Oktapiani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This abstract discusses the relevance of various 21st-century learning approaches in meeting the needs of students in the era of the digital revolution. The approaches discussed include collaborative learning, project-based learning, problem-based learning, discovery learning, inquiry-based learning, and contextual approaches. Each approach plays a crucial role in enhancing the understanding of academic content and developing much-needed 21st-century skills, such as critical thinking, creativity, collaboration, communication, digital literacy, problem-solving, and independent learning. In the context of history learning, the application of these approaches provides opportunities for students to learn actively through various methods, such as digital simulations, virtual history exhibitions, and digital document analysis. Furthermore, these approaches enable students to gain deeper and more contextual learning experiences, which are beneficial not only for understanding historical material but also for honing skills relevant to the demands of the modern world. The results of this study indicate that the integration of 21st-century learning approaches is highly relevant in preparing students to become an adaptive, innovative, and competent generation in facing the challenges faced in a world increasingly filled with technology and information.